2015
DOI: 10.1161/circep.114.001721
|View full text |Cite
|
Sign up to set email alerts
|

Is Ablation to Termination the Best Strategy for Ablation of Persistent Atrial Fibrillation?

Abstract: A lthough effective results are attained with paroxysmal atrial fibrillation (AF) ablation based on pulmonary vein isolation (PVI), catheter ablation of persistent AF remains a challenging task. Current ablation approaches in persistent AF ablation are markedly diverse, and there is a considerable variation in the reported clinical outcomes.1 Moreover, the lack of a distinct procedural end point makes comparison between the studies difficult. Response by Latchamsetty and Oral on p 971Recently, significant adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Although termination of AF has been shown by some to be predictive of longer-term outcome, other studies have not confirmed this finding. 399 , 400 , 401 , 515 , 621 , 641 , 642 It is unclear whether acute, intraprocedural termination is a true indication of procedural success, or simply might indicate patients with less persistent AF who are destined to do better regardless of the approach used. A substudy of the STAR AF II trial has suggested this latter point.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…Although termination of AF has been shown by some to be predictive of longer-term outcome, other studies have not confirmed this finding. 399 , 400 , 401 , 515 , 621 , 641 , 642 It is unclear whether acute, intraprocedural termination is a true indication of procedural success, or simply might indicate patients with less persistent AF who are destined to do better regardless of the approach used. A substudy of the STAR AF II trial has suggested this latter point.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…In this report, we successfully applied our FS detection algorithm in real time and demonstrated persistent AF termination during FS ablation at the base of the LAA after PV antral ablation. Although AF termination has been associated with improved AF-free survival postablation, 2 this end point is not yet a reproducible benchmark of long-term success. Therefore, we intend to complete 1-year clinical follow-up to assess the efficacy of our adjuvant ablation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Ablation strategies beyond pulmonary vein (PV) isolation (PVI) have not been shown to provide incremental benefit in terms of maintaining sinus rhythm 1 . However, there are data suggesting that acute termination of AF during ablation of extra-PV sources could lead to improved freedom from AF recurrence 2 . As such, there is intense interest to better characterize and identify such potential “drivers” of AF, which may be amenable to ablation and improve outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, PVI ablation alone was sufficient for an acute response -and hence the optimal ablation approach -for 20% of the virtual patient models. Lim et al (2015) reported a higher acute AF termination rate with PVI of 30-60% across multiple clinical trials. This value may be lower in our study because we only studied the ability of the atria to sustain rather than initiate AF; the significant impact of trigger removal on outcome is therefore not captured by our current model.…”
Section: Anatomical Ablation Approachesmentioning
confidence: 99%
“…We only included 50 patient-specific models which are insufficient to predict optimal ablation pattern for the six approaches simulated. We simulated and predicted acute outcome, which while correlated with, is not equivalent to long term outcome (Lim et al, 2015). We joined ablated regions to their closest region with additional ablation lines to avoid islands of ablated tissue causing re-entry; however, how best to do this requires further investigation.…”
Section: Limitationsmentioning
confidence: 99%